THE IMPACT OF CRYOPRESERVATION ON THE MORPHOLOGICAL, BIOMECHANICAL, AND REPRODUCTIVE CHARACTERISTICS OF HUMAN OOCYTES - Rasulov , Kh.A.; Yuldasheva , S.Z.; Kuziboev (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Cryopreservation of oocytes is an important tool in reproductive medicine, allowing to preserve fertility in women with cancer, endometriosis, and reduced ovarian reserve. In recent years, the vitrification method has become the standard for cryopreservation due to its high freezing rate and minimization of ice crystal formation. However, studies show that this process can cause changes in the morphological, biomechanical, and reproductive characteristics of oocytes. The present study analyzes the effect of cryopreservation on the morphology, mechanical properties, and reproductive potential of oocytes.